GP trainees' experience, knowledge and attitudes towards caring for refugees, asylum seekers and undocumented migrants. Issue 5 (3rd September 2019) - Scott, Rosie; Forde, Emer; Wedderburn, Clare
ABSTRACT: Context : According to the World Health Organisation 'more people are on the move now than ever before with an estimated 1 billion migrants in the world today and 68 million forcibly displaced people'. GPs are on the frontline of healthcare in the UK and have a responsibility to provide free and equitable access for everyone. Aim : The main aim of our work was to assess GP trainees' current experience, knowledge and attitudes towards caring for refugees, asylum seekers and undocumented migrants. Description : 30 final year GP trainees on the Dorset Vocational Training Scheme (VTS) were asked to participate by completing a questionnaire. Outcomes : The results show that GP trainees lack knowledge regarding migrants health needs, rights to care, including whether there is a duty to disclose an illegal immigrant and what to do if a patient could not provide proof of identification. They lacked experience and confidence in caring for this group of patients, with the biggest perceived challenge being language barriers. Conclusions : Education in primary care needs to respond to meet the challenge of population movement (5), and this project highlighted a need to improve education on migrants' rights to care, local support groups, as well as common health problems. In response, we have reviewed our curriculum and introduced an education session on refugee health for all our GP trainees in Dorset.